ANALISIS HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN KUALITAS TIDUR PADA REMAJA - Woran, Kezia; Kundre, Rina M; Pondaag, Ferlan A (JURNAL KEPERAWATAN, 2020)
Abstract: Social media is an online platform through internet-based applications and most of the users are Adolescents. Adolescent habits of spending a long time using social media caused disruption of rest and sleep patterns resulting poor quality of sleepr. The purpose of this study was to determine the relationship between the usage of social media and sleep quality of Adolescents in grade XI Mathematics and Sciences State Senior High School 1 Langowan. This study used descriptive analytic with Cross Sectional Study approach. The sampling technique used purposive sampling with a total sample of 80 Adolescents. The Result of statistical test studies using the Fisher Exact test and obtained a significant value Ï = 0,000 < Î± = 0.05. This study concluded there was a relationship between the use of social media and sleep quality in adolescents in class XI Mathematics and Sciences State Senior High School 1 Langowan. This study recommend that adolescents will be able to reduce the use of social media and be able to manage the rest and sleep patterns, for schools and parents to continue watching and educating adolescents in using social media.Â Key Words : Social Media, Sleep Quality, AdolescentsÂ Abstrak: Media sosial merupakan sebuah media online melalui aplikasi berbasis internet dan untuk pengguna terbanyak adalah remaja. Kebiasaan remaja menghabiskan waktu yang cukup lama untuk menggunakan media sosial mengakibatkan terganggunya pola istirahat dan tidur sehingga kualitas tidur menjadi buruk. Tujuan untuk mengetahui hubungan PenggunaanÂ  media sosial dengan Kualitas tidur pada remaja di kelas XI Matematika Ilmu Alam (MIA) SMA N 1 Langowan. Desain Penelitian yang digunakan yaitu Deskriptif Analitik dengan pendekatan Cross Sectional Study. Teknik pengambilan sampel menggunakan Purposive Sampling dengan jumlah sampel sebanyak 80 remaja. Hasil Penelitian uji statistik menggunakan uji Fisher Exact dan didapatkan nilai signifikan Ï Value = 0,000 < Î± = 0,05. Kesimpulan terdapat hubungan antara penggunaan media sosial dan kualitas tidur pada remaja dikelas XI Matematika Ilmu Alam (MIA) SMA N 1 Langowan. Saran diharapkan remaja mampu mengurangi penggunaan media sosial dan mampu memenejemen pola istirahat dan tidur, bagi pihak sekolah dan orang tua agar tetap mengawasi dan mengedukasi remaja dalam menggunakan media sosial.Â Â Â Â Â Â Â Â Â Â Â  Â Â Â Â Â Â Â Â Â Â Â Kata Kunci : Media Sosial, Kualitas Tidur, Remaja